Proceedings of the XXth Congress of the International Society of Biomechanics and the 29th Annual Meeting of the American Society of Biomechanics, July 31 - August 5, 2005, Cleveland, Ohio (International Society of Biomechanics in Sports, 2005)
Internetversion der auf dem XX. Kongress der International Society of Biomechanics und der 29. Jahrestagung der American Society of Biomechanics am 31. Juli - 5. August 2005 in Cleveland, Ohio gehaltenen Vorträge.